Network RTK: A case study in Florida - Berber, Mustafa; Arslan, Niyazi (ELSEVIER SCI LTD, 2013)
Traditionally, in RTK (Real Time Kinematic) GPS (Global Positioning System), rovers receive RTK data from a single RTK reference station. Nonetheless, as the distance increase between the stations, range measurements become more and more uncorrelated and this limits the ability to resolve the atmospheric and orbital errors. To overcome this drawback, Network RTK concept has been developed. In Network RTK rather than only base station and rover(s), as the name indicates, there are network of reference stations. These reference stations continuously stream GNSS (Global Navigation Satellite System) data to central server running Network RTK software and these measurements are used to generate corrections for the region ideally encompassed by the reference stations using advanced interpolation techniques. It means that Network RTK covers larger area and still maintains the same level of performance. In this study, to evaluate their performance, four RTK corrections, namely, MAX, I-MAX, VRS and FKP are compared. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Real Time Kinematic GPS; Network RTK; RTK corrections; Virtual reference station; Master-auxiliary concept; Engineering; Instruments & Instrumentation